Escin’s phytochemistry and pharmacy: biosynthesis, chemistry, synergism and novel activities - Fazliev, Sunnatullo; Tursunov, Khurshid; Sharipov, Avez; Xaydarov, Vosiljon; Normakhamatov, Nodirali; Rizaev, Kamal; Wang, Tianfu; Aisa, Haji Akber (Phytochemistry reviews, 2024)
Drug resistance against antibiotics and cancer chemotherapeutics are one of the pressing issues before contemporary medicine. One way to overcome drug resistance-administration of multiple drugs called “polypharmacy” has its own problems and concerns. Combining drugs in a single formulation to increase therapeutic efficacy through synergistic effects and enhanced sensitivity is becoming popular nowadays. This approach allows to combine various drugs, especially natural product-based compounds to achieve decreased toxicity and increased bioavailability. In addition, drug delivery is another powerful way to increase therapeutic efficacy and minimise adverse effects of drugs. Furthermore, novel activities of already used drugs are being discovered through combinatorial approaches and network pharmacology. Escin, plant derived triterpenoid saponins, certainly offers a great platform when it comes to combination drugs. Besides potent anti-cancer, anti-inflammatory and anti-oedematous effects, recent years have seen a number of publications reporting various pharmacological activities of drug combinations containing escin. Moreover, as a natural biosurfactant, escin can also be used in drug delivery systems. In this review we focus on escin as a natural adjunct compound in various combination drug formulations, drug delivery vehicles and explore synergistic and novel activities arising from such combined drugs. We comprehensively discuss and present an overview of geography, sources, functions in flora, extraction methods, biosynthesis and chemistry of escin isomers. We then delve into pharmacological activities as well as in vitro and in vivo studies of combination drugs with escin. We end the review with concluding remarks, open questions and possible future directions of the field.